RECENT HEAVY-ION EXPERIMENTS AND STATISTICAL-MODEL OF HADRONS - Dey, J.; Krein, G.; Tomio, L.; Frederico, T. (Springer, 1994)
The combined CERN and Brookhaven heavy ion (H.I.) data supports a scenario of hadron gas which is in chemical and thermal equilibrium at a temperature T of about 140 MeV. Using the Brown-Stachel-Welke model (which gives 150 MeV) we show that in this scenario, the hot nucleons have mass 3 pi T and the pi and rho mesons have masses close to pi T and 2 pi T, respectively. A simple model with pions and quarks supports the co-existence of two phases in these heavy ion experiments, suggesting a second order phase transition. The masses of the pion, rho and the nucleon are intriguingly close to the lattice screening masses.